Pastoral Strategies for the Loneliness Epidemic of the Digital Generation - Gultom, Joni Manumpak Parulian; Simanjuntak, Fredy (Sekolah Tinggi Theologia Jaffray, 2022)
In the frenzy of technological advances and the massive capabilities of social media, it turns out that there is a dangerous space that this generation often doesn't realize, namely loneliness. Since the discovery of internet technology, lonely sufferers have experienced a spike among digital people. They often feel lonely and seemingly asymptomatic. If pastoral stewardship does not address this problem, the digital generation is bound to feel lonely and depressed, which can lead to suicide. They experience a decreased quality of life despite being in the church and parental care. The question is, what are the causes and effects of this problem of loneliness? What practical steps can shepherds take? And what kind of pastoral strategy is there to tackle the loneliness epidemic ravaging the digital generation? The purpose of this study is [1] to describe the causes and adverse effects of loneliness problems. [2] Describe simply practical steps a shepherd can take in dealing with loneliness. [3] Describe her pastoral and stewardship strategies that a solution to the problem of loneliness among this digital generation. The method used in this research is Systematic Literature Review (SLR) for journal papers published in 2016-2021. Contribution of this research ; [1] For spiritual practitioners and educators who are directly related to recovery from the loneliness of the digital generation, [2] as a reference for pastoral teams and pastoral candidates in local church stewardship, [3] practical steps for parents in overcoming loneliness problems digital child they experienced.